2010
DOI: 10.1093/molbev/msq312
|View full text |Cite
|
Sign up to set email alerts
|

Y-Chromosomal Variation in Sub-Saharan Africa: Insights Into the History of Niger-Congo Groups

Abstract: Technological and cultural innovations as well as climate changes are thought to have influenced the diffusion of major language phyla in sub-Saharan Africa. The most widespread and the richest in diversity is the Niger-Congo phylum, thought to have originated in West Africa ∼ 10,000 years ago (ya). The expansion of Bantu languages (a family within the Niger-Congo phylum) ∼ 5,000 ya represents a major event in the past demography of the continent. Many previous studies on Y chromosomal variation in Africa asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 52 publications
8
148
0
Order By: Relevance
“…However, this scenario of a slow and gradual process of diversification over short distances does not fit well with the evidence for a demic migration apparent in the reduction of diversity values for the genetic markers, nor with the low genetic distance values among geographically distant Bantu groups. An alternative explanation could be that the signal of the initial migration(s) might have been attenuated by later contact among peoples and languages, as suggested by previous genetic studies of mtDNA [35,36], Y-chromosomal [18] and autosomal [32] markers. This hypothesis finds some support in our data, since the linguistic distances between Eastern and Western languages belonging to adjacent Guthrie's zones (such as K versus M) are significantly smaller compared with those of non-adjacent zones (such as H-R versus G-P, K versus G-P and H-R versus M; all MWUs with one tail p , 10 214 ; data not shown).…”
Section: Discussion (A) Demic Diffusion Of Bantu-speaking Peoplesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this scenario of a slow and gradual process of diversification over short distances does not fit well with the evidence for a demic migration apparent in the reduction of diversity values for the genetic markers, nor with the low genetic distance values among geographically distant Bantu groups. An alternative explanation could be that the signal of the initial migration(s) might have been attenuated by later contact among peoples and languages, as suggested by previous genetic studies of mtDNA [35,36], Y-chromosomal [18] and autosomal [32] markers. This hypothesis finds some support in our data, since the linguistic distances between Eastern and Western languages belonging to adjacent Guthrie's zones (such as K versus M) are significantly smaller compared with those of non-adjacent zones (such as H-R versus G-P, K versus G-P and H-R versus M; all MWUs with one tail p , 10 214 ; data not shown).…”
Section: Discussion (A) Demic Diffusion Of Bantu-speaking Peoplesmentioning
confidence: 99%
“…Genetic studies have highlighted the strong demographic impact of the Bantu migration on the gene pool of Sub-Saharan African populations for mtDNA [15,16], the Y chromosome [17,18] and autosomes [19,20]. However, a recent study by Sikora et al [21] of approximately 2800 autosomal single nucleotide polymorphisms suggested that the spread of Bantu languages to southeastern Africa (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The Western Cape Province of South Africa has a rich genetic history, arising from many parts of the world including the local ancient Khoisan population [8][9][10][11] , the greater Bantu groups from the Niger-Congo phylum 12,[14][15][16] , European settlers 17,18 and slaves from the East 18,19 . Marriages amongst the different population groups were once common 17,20 , and produced a heterogeneous new and genetically unique population in the Western Cape, until apartheid was introduced and resulted in a drastic decrease in cross-population gene flow 6,20,25 .…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Variants from this Bantu family in the south included the Nguni group (Xhosa, Zulu, Swati and Ndebele tribes) and the Southern (also called the Sotho-Tswana) groups (Southern Sotho, Northern Sotho, Tswana, Venda and Tsonga tribes). 12,14,15 The Nguni populations migrated southwards over many centuries with large herds of Nguni cattle. These migration patterns started around 2000 years ago followed by larger migration impressions around 1400 CE.…”
Section: Population Demographic Originmentioning
confidence: 99%
See 1 more Smart Citation